Karakteristik Kondisi Geologi Daerah Lamo, Kecamatan Pagimana, Kabupaten Banggai, Provinsi Sulawesi Tengah. - Ariyanto Pakaya; Yayu Indriati Arifin; Ninasafitri Ninasafitri (Universitas Negeri Gorontalo, 2026)
The East Arm of Sulawesi is an active tectonic zone formed by the collision between the Banggai-Sula microcontinent fragments and the East Sulawesi Ophiolite Complex. This research was conducted in Lamo Village and its surrounding areas, Pagimana District, Banggai Regency, to identify detailed geomorphological, lithostratigraphic, and structural geology characteristics, which currently remain limited. The research methods include field mapping, morphometric analysis using DEMNAS data and structural kinematic analysis using stereographic projection. The results indicate that the geomorphology of the study area is divided into two units: the Structural Hills Unit (slope 2–50%) and the Coastal Plain Unit (slope 0–2%). Lithostratigraphically, the study area consists of a Peridotite Unit covering 23.81 km² and an Alluvial Unit covering 1.83 km². Structural analysis of the Peridotite Unit reveals a high intensity of extension joints with a maximum principal stress (σ1) oriented at 127°/71° (NW–SE).